Analytical methods for assessing changes induced by gamma exposure in an animal model - Mingote,Matheus F. Soares (2020)
SUMMARY OBJECTIVE: Ionizing radiation can cause radio-induced changes in the cellular metabolome due to the breakdown of DNA bonds. Our goal was to find the early tissue response to radiation exposure supported by distinct analytical methods. METHODS: Histological analyses were performed on the organs extracted from rats to search for microscopic changes. The histological slides stained with hematoxyline-eosin (HE) were analyzed in magnification (40x). Subsequently, the tissues were subjected to mass spectrometry that allowed molecular analysis and DESI-MSI that generated the molecular image of lipids, assessing changes in intensities, especially in the brain. RESULTS: The histological analysis found nonspecific inflammatory changes; no areas of fibrosis, necrosis, or apoptosis were identified, suggesting non-morphological tissue alterations. However, the DESI-MSI images of brain lipids allowed the observation of many radio-induced changes in the lipid's intensities. CONCLUSIONS: No early radio induced histological or mass weight changes in the radiation exposed rats could be observed at 5 Gy. However, early changes in the molecular level were observed in the DESI-MSI images of the brain lipids. The DESI-MSI method proved to be efficient and relevant, allowing a regional molecular analysis of the tissues, expanding a new field of study that is still in its infancy: radiometabolomics.